Pelatihan Membaca Kitab Kuning bagi Penghulu Kementerian Agama Kabupaten Luwu Utara - Mardi Takwim; Mustafa Mustafa; Kartini Kartini; Andi Arif Pamessangi; Naidin Syamsuddin (Universitas Andi Djemma, 2021)
AbstrakPenghulu adalah pegawai negeri sipil sebagai pegawai pencatat nikah yang diberi tugas, tanggung jawab, wewenang, dan hak secara penuh oleh Menteri Agama atau pejabat yang ditunjuk sesuai dengan peraturan perundang-undangan yang berlaku untuk melakukan pengawasan nikah/rujuk menurut agama Islam dan kegiatan kepenghuluan. Masalah yang akan diselesaikan dalam kegiatan ini adalah (1) Bagaimana teknik penyajian pelatihan baca kitab kuning (2) Bagaimana materi yang sesuai dengan kebutuhan peserta pelatihan baca kitab kuning (3) Bagaimana tindak lanjut atau pendampingan pelatihan baca kitab kuning bagi penghulu kementerian agama di Kabupaten Luwu Utara. Tujuan dalam kegiatan pengabdian ini menjelaskan teknik penyajian pelatihan baca kitab kuning, menyampaikan materi yang sesuai dengan kebutuhan peserta pelatihan baca kitab kuning dan menindaklanjuti atau melakukan pendampingan pelatihan baca kitab kuning bagi penghulu kementerian agama di Kabupaten Luwu Utara. Metode yang dipergunakan dalam pengabdian ini terdiri atas pemaberian materi, praktik dan pendampingan. Hasil dari kegiatan ini yang sudah dilakukan terdapat peningkatan pemahaman peserta dalam pengenalan kata benda, kata kerja dan huruf yang ada dikitab kuning selain itu peserta sudah dapat memahami perubahan baris dan perubahan kata kerja, jumlah fi’liyah, jumlah ismiyah, unsur pelengkap dalam kalimat dan kaidah-kaidah maupun contoh kaidah dalam kitab kuning yang disajikan oleh tim pelaksana kegiatan. Selain terdapat tingkat kepuasan peserta dalam mengikuti kegiatan Pelatihan Membaca Kitab Kuning.Kata Kunci: Kitab Kuning, PenghuluAbstractPenghulu is a civil servant as a marriage registrar who is given full duties, responsibilities, authority, and rights by the Minister of Religion or an appointed official by applicable laws and regulations to carry out marriage supervision/reconciliation according to the Islamic religion and penghulu activities. The problems that will be solved in this activity are (1) How is the presentation technique of reading the yellow book training (2) How is the material according to the needs of the yellow book reading training participants (3) How is the follow-up or assistance for reading the yellow book training for the head of the ministry of religion in the Regency North Luwu. The purpose of this service activity is to explain the technique of presenting the yellow book reading training, deliver materials that are by the needs of the yellow book reading training participants and follow up or provide assistance to the yellow book reading training for the head of the ministry of religion in North Luwu Regency. The method used in this service consists of providing material, practice, and mentoring. The results of this activity that have been carried out have increased participants' understanding in the introduction of nouns, verbs, and letters in the yellow book, besides that participants can understand line changes and verb changes, the number of aliyah, the number of ismiyah, complementary elements in sentences and the rules and examples of rules in the yellow book presented by the activity implementation team. In addition, there is a level of satisfaction of participants in participating in the Yellow Book Reading Training activity.Keywords: Yellow Book, Penghulu.